Udział nauczycieli-wychowawców w kształtowaniu zachowań prospołecznych uczniów szkół średnich w dobie przesileń zachodzących we współczesnym świecie - Wereszczyńska, Katarzyna (Rocznik Pedagogiczny, 2022)
The first part of the article includes definitions and interpretations of such categories as class teacher, prosocial behaviour and prosocial upbringing as well as explains the term upheaval – an era of numerous crises as well as deficits occurring in human behaviour. The following section of paper presents a few selected reflections of pedagogical scholars as well as scholars representing other fields of science, i.e. critical observers of reality who are not indifferent to the problems of the contemporary world and the need for upbringing which could help people to become better. The author’s research was designed to find out how class teachers and the schools are engaged in today’s upbringing measures, with the aim of promoting and shaping students’ active prosocial behaviour. A survey-based research was conducted at 24 schools in the Opole Province between 2018 and 2019. The participants were teachers of secondary school graduation classes and principals of schools included in the research. The article presents chosen research results. In the final part, author’s observations are made in the light of the opinions of the scholars indicating the need for and importance of upbringing a person to enjoy harmonious relations with others. Comments and conclusions derived from author’s research are also included.